جدلية السياسي والاداري في صنع السياسة العامة في الجزائر ( 2009-2019) - كحيل, امال (جامعة الوادي university el-oued)
"الملخص: تعد جدلية السياسي والإداري في عملية صنع السياسة العامة، من المواضيع المهمة ضمن حقل العلوم السياسية والإدارة العامة، ومن هذا المنطلق قمنا بالاهتمام بهذا الموضوع في إطار الإجابة عن التساؤل الرئيسي، الذي يبحث فيما كان السياسي هو الفاعل المؤثر أكثر في صنع السياسة العامة أم الإداري وذلك في إطار التشابك والغموض الذي تتميز به العلاقة بينهما، فخصصنا الفصل الأول لتحديد المفاهيم والفصل الثاني تطرقنا فيه إلى دراسة وتحليل هذه العلاقة وأثرها على عملية صنع السياسة العامة في الجزائر، ولقد توصنا إلى مجموعة من النتائج أهمها هي سيطرة السياسيين على هذه العملية السياسية، واستبعاد كل من الإداريين والمختصين من هذا المجال. ويبقى مجال البحث وآفاقه واسعة أمام الباحثين والدارسين لإثراء هذا الموضوع. ""Summary: The political and administrative dialectic in the public policy-making process is one of the important topics within the field of political science and public administration, and from this point of view we have paid attention to this topic within the framework of the answer to the main question, which examines whether the politician was the most influential actor in making public or administrative policy. In the context of the intertwining and ambiguity that characterizes the relationship between them, we devoted the first chapter to defining concepts and the second chapter in which we dealt with the study and analysis of this relationship and its impact on the process of public policy-making in Algeria, and we reached a set of results, the most important of which is the control of politicians over this political process, and the exclusion of all Of administrators and specialists from this field. The field of research and its horizons remains wide for researchers and scholars to enrich this topic. "
Keywords: علاقة السياسي بالاداري - صنع السياسة العامة .; Relationship between political and administrative - Public policy making.